A Supramolecular [10]CPP Junction Enables Efficient Electron Transfer in Modular Porphyrin–[10]CPP⊃Fullerene Complexes. Issue 36 (6th August 2018) - Xu, Youzhi; Wang, Bingzhe; Kaur, Ramandeep; Minameyer, Martin B.; Bothe, Michael; Drewello, Thomas; Guldi, Dirk M.; von Delius, Max
Abstract: Efficient photoinduced electron transfer was observed across a [10]cycloparaphenylene ([10]CPP) moiety that serves as a rigid non‐covalent bridge between a zinc porphyrin and a range of fullerenes. The preparation of iodo‐[10]CPP is the key to the synthesis of a porphyrin–[10]CPP conjugate, which binds C60, C70, (C60 )2, and other fullerenes ( K A >10 5 m −1 ). Fluorescence and pump–probe spectroscopy revealed intramolecular energy transfer between CPP and porphyrin and also efficient charge separation between porphyrin and fullerenes, affording up to 0.5 μs lifetime charge‐separated states. The advantage of this approach towards electron donor–acceptor dyads is evident in the case of dumbbell‐shaped (C60 )2, which gave intricate charge‐transfer behavior in 1:1 and 2:1 complexes. These results suggest that [10]CPP and its cross‐coupled derivatives could act as supramolecular mediators of charge transport in organic electronic devices. Abstract : Modular dyads : The successful synthesis of iodo‐[10]CPP allowed the study of photoinduced electron transfer in unusual supramolecular porphyrin–[10]CPP⊃fullerene complexes.